Libraries and Print Culture in Early North Carolina - Valentine, Patrick M. (My University, 2005)
Print culture in colonial North Carolina was more robust than most people think. Early North Carolinians soon built up their private collections into sometimes substantial libraries. Studying print through the agency of libraries gives new historical insights into colonial society.
Keywords: Colonial North Carolina libraries print